Motivasi Siswa dalam Mengikuti Pembelajaran Permainan Bola Basket di Kelas VIII SMP Negeri 3 Banjarmasin - Huda, Abdi Nul; Fauzan, Lazuardy Akbar; Dirgantoro, Edwin Wahyu (MAN Insan Cendekia Jambi, 2025)
This study aims to determine the level of student motivation in participating in basketball game learning at SMPN 3 Banjarmasin. The research uses a descriptive quantitative method with a population of 282 eighth-grade students at SMPN 3 Banjarmasin who take part in basketball game learning, and a sample of 80 students. The sampling technique used in this study is simple random sampling. The instrument used for data collection is a questionnaire. Based on the results of the study, it can be concluded that students’ motivation in participating in basketball game learning falls into the moderate category with a percentage of 43%. The factors that significantly influence the level of motivation are intrinsic factors, especially the indicator of attention (54%), and extrinsic factors, particularly the school indicator (49%). It can be concluded that out of the 80 students who participated as research samples, their motivation to participate in basketball game learning in eighth grade at SMPN 3 Banjarmasin is categorized as moderate.